Assessment of Sewage Molecular Markers: Linear Alkylbenzenes in Sediments of an Industrialized Region in Peninsular Malaysia - Alkhadher S.A.A.; Al-Hazmi H.E.; Suratman S.; Zakaria M.P.; Masood N.; Szel?g B.; Magam S.M.; Al-Qadami E.H.H.; Majtacz J.; Kowal P.; Kurniawan T.A.; Abdulrahman S.A.M.; et al. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
In this study, the use of linear alkylbenzenes (LABs) was employed to pinpoint the sources of human activity that cause detrimental impacts on the coastal environment and river ecosystems. LABs were detected using GCMS in sediment samples assembled from Kim Kim River (KKR) and the Port Dickson coast (PDC). To assess the significance of variations in the distribution and concentrations of LABs across the sampling sites, this study utilized several statistical techniques such as post hoc tests, LSD techniques, analysis of variance (ANOVA), and the Pearson correlation coefficient using a significance level of p < 0.05. The degradation levels of LABs and wastewater treatment were assessed in the study using internal congeners (I/E), homologs of C13 and C12, and long-to-short-chain (L/S) ratios. The results revealed that the LAB concentrations varied between 88.3 and 112 ng/g dw in KKR and 119 to 256 ng/g dw in the PDC. Most of the surveyed areas exhibited a substantial count of C13LABs homologs that displayed a significant difference (p < 0.05). The I/E ratios ranged from 1.7 to 2.0 in KKR and from 2.0 to 4.1 in the PDC, suggesting that the effluents originated from sources associated with the physical phase and biological phase in wastewater treatment systems (WWTSs). The results revealed that the degradation of LABs varied between 34% and 38% in KKR and between 40% and 64% in the PDC. This study underscores the importance of ongoing improvements to WWTSs and emphasizes the potential of LABs as indicators for monitoring wastewater contamination. 2023 by the authors.